Comparative Analysis of Weather Radar Signatures of Puting Beliung in Indonesia - Kiki; Koesmaryono, Yonny; Hidayat, Rahmat; Sukma Permana, Donaldi; Perdinan (Jurnal Meteorologi dan Geofisika, 2025)
This study presents a comprehensive radar-based analysis of Puting Beliung (PB), Indonesia’s localized tornado phenomenon, using multiple weather radar–derived products. A comparative analysis of ten PB cases was conducted to identify consistent meteorological signatures and variations in tropical storm behavior, motivated by recent observations indicating an increasing frequency of PB events in Indonesia and the need for improved detection methods. Analysis using Rainbow software reveals consistently high reflectivity values ranging from 35 to 60 dBZ, with diverse echo patterns, among which the hook echo is the most dominant. Physical parameters show horizontal wind speeds of 10–30 knots at an altitude of 4 km, horizontal shear of 5–10 m s⁻¹ km⁻¹, and vertical shear of 1–10 m s⁻¹ km⁻¹, while spectral width analysis indicates moderate turbulence with values around 3 m s⁻¹. The Tornadic Vortex Detection (TVD) product identifies potential vortex signatures at six locations, with detected heights ranging from 1.2 to 3.1 km. This study represents the first comprehensive application of multiple radar products for PB characterization in Indonesia and identifies CMAX, HWIND, HSHEAR, and TVD as the most effective products for PB detection and monitoring. These findings provide essential baseline criteria for the development of radar-based early warning systems tailored to Indonesia’s tropical environment, with the potential to reduce the socioeconomic impacts of PB events through improved detection and prediction capabilities.